Analysis of Student Perceptions Regarding the Implementation of the STEM-Quran Approach to Science Subject in Junior High School - Kofifah Silfanah; Septi Budi Sartika (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
STEM (Science, Technology, Engineering, and Mathematics) education has been widely recognized as an effective approach to improve science and technology literacy among students. However, the integration of STEM with Quranic values (STEM-Quran) is a relatively new concept and has not been widely researched. This study aims to determine students' perceptions related to the application of the STEM-Quran approach in science subjects. The quantitative method and a descriptive survey used in this study. The sampling technique using random techniques obtained 80 students from a junior high school in Sidoarjo, Indonesia. The instrument used was a questionnaire of student perceptions related to the application of the STEM-Quran approach in science subjects. Data analysis techniques using descriptive statistical tests with the TCR (Respondent Achievement Rate) method. Based on the results of data analysis, it is concluded that the perceptions of students towards the STEM-Quran approach are generally in the good category. The STEM-Quran approach in schools that have not implemented it is a step forward that has the potential to improve the quality of education, implement a more effective approach, and integrate spiritual and academic aspects in science learning, thereby improving students' learning experiences and outcomes.